Whiteboard Animation Learning Media on Economic Activity Material for Grade IV Elementary Schools - Fadhlurrohman, Naufal Aziz; Bektiningsih, Kurniana (Universitas Pendidikan Ganesha, 2024)
Based on the observations made by researchers in class IV elementary schools, it is proven that there are problems in the learning process and the need for more types and kinds of learning media used, one of which is the Natural and Social Sciences (IPAS) learning content. The researcher conducted this research to develop creative and innovative learning media to foster students' higher interest in learning. This research aims to develop learning media and find out the feasibility of this media and the effectiveness of whiteboard animation learning media on economic activity material for science and science learning content. The research used by researchers uses the Research and Development (R&D) method and the method used uses the ADDIE method. Then, researchers collected data through observation, interviews, and student learning results. The subjects in this research are students, teachers, and a team of experts (media experts and material experts). Qualitative descriptive techniques, quantitative descriptive techniques, and differential statistics are techniques for analyzing data in the development of this learning media. The results obtained in this research were from the media expert test 90%, material expert test 92%, teacher test 90%, small group test 91.25%, large group test 95%, as well as the results of the pre-test and post-test to test the effectiveness of the media used developed that has very feasible results from both small and large groups. The results of N-gain state that the whiteboard animation media has a suitable category for use in the learning process of economic activity material with IPAS content